In vivo evaluation of sweet potato leaf (Ipomoea batatas (L.)Lam.) extracts for treatment of psoriasis using mouse model - Sani, Anuar (2017)
Psoriasis is a complex genetic disease involving both autoimmune and inflammatory components though its exact aetiology remains unknown. It is prevalent worldwide and affects both men and women over a wide age range. In Malaysia, about 4% of the population are affected. Topical medications especially corticosteroids are used for localised disease. Phototherapy and climatotherapy are effective for more extensive disease. Systemic therapies are reserved for patients with refractory disease. The use of complementary and alternative medicines is also common among psoriasis patients. In Malaysia, sweet potato leaves have been used as an alternative therapy for psoriasis. In light of these subjective observations and under continuous pressure of finding new remedies to meet the unmet needs in psoriasis treatment, the researcher examined two different extracts derived from sweet potato leaves against experimentally induced psoriasis aiming to draw a distinction between the patients’ subjective observations and the scientific evidence, risks and benefits of treatments. This study offered a novel research based on examination of lipophilic and hydrophilic extracts from sweet potato leaves (SPL) of Gendut MSP94 cultivar in experimental animal model. The hydrophilic (ethanolic) extraction of SPL was done based on the protocol described by Park et al. (2010). The Lipophilic (hexane) extraction was based on the protocol described by Teow et al. (2007). The concentrated extracts obtained were in the form of thick dark greenish pastes which were ideal for direct application onto the induced psoriasis. Hydrophilic extract showed high levels of chlorogenic and caffeic acids which were similar to earlier studies. However, it is strongly recommended that ultra-analysis of Gendut SPL extracts should be considered in the future studies to define the traces of bioactive chemicals not been identified in the current research, as it was beyond its scope. The total phenolic content of Gendut SPL ethanolic extracts was assessed using Amin et al. (2004) protocol. It was found to be nearly 50% of the values obtained from other studies done on different cultivars of sweet potatoes. The mouse model of psoriasis was induced chemically by topical Imiquimoid onto shaved skin of BALB/c mice, following the same protocol described by van der Fits et al. (2009). Histologically, the resulting lesions were typical to human’s psoriasis vulgaris as confirmed by dermatologist and histopathologist.Flow cytometry showed increased levels of CD3+, CD4+ and CD8+ cells and TNF-alpha in the peripheral blood which were signs of inflammatory reaction seen in acute psoriasis.Upon treatment, results showed significant clinical improvement in the lipophilic SPL extract-treated group, as scored by modified PASI, compared to hydrophilic SPL extract-treated and negative control groups. Histopathological changes showed significant decrease of epidermal thickness and rete ridges. Immunological and molecular parameters showed significant decrease in the inflammatory biomarkers namely TNF-alpha and the percentage of double negative T cells. In conclusion, this study shows a substantial evidence of anti-psoriatic properties of SPL lipophilic extract that should encourage us to look further into its active compound(s) responsible for the effects.